The concept “Prairie” in the novel “Riders” (“Vershnyky”) by Yu. Yanovskyi (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2017)
The analysis of the concept “Prairie” is laid out in the article. The characteristic of space is realized through this concept in the novel “Riders” (“Vershnyky”) by Yu. Yanovskyi. The defining impact of geographical and climate factors on formation of national character, thinking of the nation and world perception is proved. Prairie in national and language picture of the world is associated in the work with infinity, openness, wideness, freedom, which have an effect on the formation of long-standing historical experience of Ukrainian people. East, central and southern regions of Ukraine are presented (nowadays Dnipropetrovsk, Donetsk, Zaporizhzhia, Kirovohrad, Mykolayiv, Odessa, Poltava, Kherson districts, Crimea) bound with the Black Sea and the Milky Way (Chumatskyi Shliakh). Infinity and eternity of great Ukrainian prairie is emphasized by boundlessness, immensity of space height and mistery: the Milky Way (Chumatskyi Shliakh), star patterns Pleiades (Volosozhar or Stozhary or Pleiiady; also known as Baby-Zvizdy, Kvochka), Cynosure (Viz), Aquila (Divka z vidramy – the Ukrainian variant for Aquila). It is the universe of the nation, severe and fantastic land on four winds (maistros, grego, tramontane, whirlwind-spindle), which was discovered by the prairie people in the harmony of sounds, smells, tastes, visual objects, in the sense of inexhaustibility of native land wealth, immensity of freedom, heady freedom between blue towers of blue sky and fascinating, fantastic wild prairie, that became the first memory from childhood, motherland, where different events happened: tragic social storms of global level as prairie in winter or during storm, serene calm life of buckwheatseeders or fishermen as incandescent prairie that dings of heat and silence. Such a feeling of “crazy exaltation” has formed the national character of Ukrainian people during centuries and, maybe, it has affected historical fate of the nation.
Keywords: anthropological linguistics; linguocultural studies; concept,; national and language picture of the world